2003
DOI: 10.1007/s10126-002-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

RecA-Mediated, Targeted Mutagenesis in Zebrafish

Abstract: Abstract:We have evaluated the efficacy of RecA, a prokaryotic protein involved with homologous recombination, to direct site-specific mutagenesis in zebrafish embryos. For this we coinjected a vector containing a mutated enhanced green fluorescent protein (EGFP) gene plus 236-nucleotide corrective single-stranded DNAs coated with RecA into 1-cell zebrafish embryos. Twenty-hours after fertilization, about 5% to 20% of injected embryos showed EGFP expression in 1 or more cells when RecA-coated corrective DNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…A stable potential knockout/knockin line could be generated and bred to homozygosity until the F 3 generation. The rate of homologous recombination with the characteristic of germ line transmission was 1.7Â10 _ 6 in this study, which was close to the results previously described (Cui et al, 2003). Even so, the method established here can still be regarded as efficient and practical for the manipulation of genes in zebrafish without embryonic stem (ES) cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A stable potential knockout/knockin line could be generated and bred to homozygosity until the F 3 generation. The rate of homologous recombination with the characteristic of germ line transmission was 1.7Â10 _ 6 in this study, which was close to the results previously described (Cui et al, 2003). Even so, the method established here can still be regarded as efficient and practical for the manipulation of genes in zebrafish without embryonic stem (ES) cells.…”
Section: Discussionsupporting
confidence: 75%
“…Injection of such oligonucleotides into newly fertilized eggs has highly specific effects on a wide variety of genes. Large-scale mutagenesis screening methods are available for zebrafish, allowing the identification of important genes in development and diseases (Lin et al, 1994;Gaiano et al, 1996;Cui et al, 2003). However, in comparison with the mouse, for which the gene knockout method was developed a long time ago (Bradley et al, 1984), for zebrafish the method to produce a line of targeted gene modification through homologous recombination between the introduced DNA and the corresponding chromosomal segments is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are likely more sensitive indicators of UVB damage, as 0.005 J/cm 2 was sufficient to stimulate some aspects of DNA repair in zebrafish, although the specific mechanisms have not been identified [33]. While to our knowledge, a systematic characterization of UVA dosing regimes in zebrafish embryos has not been presented, data have been gathered for responses of zebrafish to UVB as part of environmental studies.…”
Section: Uvb and Uva Sensitivities Of Zebrafishmentioning
confidence: 99%
“…Cui et al (2003) have reported RecA-mediated, targeted mutagenesis in zebrafish. Previously we have shown the possibility of drug selection for gene transfer into established piscine non-ES cell lines (Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%